Repercussion of nonsteroidal anti-inflammatory drugs on the gene expression of human osteoblasts - Melguizo-Rodríguez,Lucia; Costela-Ruiz,Víctor J.; Manzano-Moreno,Francisco J.; Illescas-Montes,Rebeca; Ramos-Torrecillas,Javier; García-Martínez,Olga; Ruiz,Concepción (PeerJ, 2018)
Background Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used in clinical practice, which can have adverse effects on the osteoblast. The objective of this study was to determine the effect of NSAIDs on the osteoblast by analyzing the gene expression of different markers related to osteoblast maturation and function when treated in vitro with different NSAIDs. Methods Three human osteoblast lines from bone samples of three healthy volunteers were treated with 10 µM acetaminophen, indomethacin, ketoprofen, diclofenac, ibuprofen, ketorolac, naproxen, and piroxicam. The gene expression of different markers (run related transcription factor 2 [RUNX-2], type 1 collagen [COL-I], osterix [OSX], osteocalcin [OSC], bone morphogenetic protein 2 [BMP-2] and 7 [BMP-7], transforming growth factor β1 [TGF-β1], and TGFβ receptors [TGFβR1, TGFβR2; TGFBR3]) were analyzed by real-time PCR at 24 h of treatment. Results Expression of RUNX-2, COL-I, OSX, was reduced by treatment with all studied NSAIDs, OSC expression was reduced by all NSAIDs except for ketoprofen, naproxen, or piroxicam. Expression of BMP-7 was reduced by all NSAIDs; BMP-2 was reduced by all except for naproxen. In general, NSAID treatment increased the expression of TGF-β1, but not of its receptors (TGFβ-R1, TGFβ-R2, andTFGβ-R3), which was either unchanged or reduced by the treatment. Conclusion These data confirm that NSAIDs can affect osteoblast physiology, suggesting their possible impact on bone.
Keywords: Bone tissue; Osteoblasts; Differentiation; Gene expression; NSAIDs